UV‐Assisted Low Temperature Oxide Dielectric Films for TFT Applications. Issue 8 (27th August 2014) - Hwang, Jaeeun; Lee, Kyungmin; Jeong, Yesul; Lee, Yong Uk; Pearson, Christopher; Petty, Michael C.; Kim, Hongdoo
<x xml:space="preserve">Abstract</x> Solution‐based oxide gate dielectric layers are prepared from metal nitrates using UV‐assisted annealing at 150 °C. The leakage current densities of ZrO2 and Al2O3 dielectrics are less than about 10‐9 A/cm2 at 1 MV/cm and comparable to those formed by annealing at higher temperatures. High dielectric constants and the low leakage current behavior of the dielectric layers provide excellent ZnO TFT performance, with a field effect mobility of 1.37 cm2/V.s and an off‐current density of 10‐12 A/cm2. This low fabrication temperature process is compatible with future plastic electronics technology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>